CT-derived characterization of pericoronary, paracardial and epicardial adipose tissue and its association with myocardial ischemia as assessed by adenosine stress CMR perfusion imaging. (13th July 2021) - Goeller, M; Duncker, H; Dey, D; Moshage, M; Bittner, D; Ammon, F; Achenbach, S; Marwan, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Kaltenbach scholarship of the german heart foundation Background: Increased attenuation of pericoronary adipose tissue (PCAT) around the right coronary artery (RCA) is a new imaging biomarker to detect coronary inflammation derived from routine coronary CT angiography (CTA) and has been shown to be associated with cardiac mortality. Increased volume of epicardial adipose tissue (EAT) has been reported be associated with myocardial ischemia. Purpose: We aimed to investigate for the first time a potential association between CTA-derived PCAT measures and myocardial ischemia as assessed by adenosine stress CMR perfusion imaging. Methods: In this single-centre study 109 stable individuals (mean age of 62 ± 11 years, 77% males) with coronary artery disease underwent CTA followed by adenosine stress CMR perfusion imaging to detect myocardial ischemia. PCAT CT attenuation (HU) and PCAT volume (cm³) was measured around the RCA (10 to 50 mm from RCA ostium), the proximal 40 mm of the left anterior descending artery (LAD) and the circumflex artery (LCX) using semi-automated software. Per patient PCAT CT attenuation was calculated as followed: (PCAT attenuation of RCA + LAD + LCX)/3). Non-contrast CT data sets were used for coronary calcium scoring and the quantification of EAT (located between the myocardial surface and the pericardium) and paracardial adipose tissue (PAT; intrathoracic and outside of the pericardium). Results: Between patients with evidence of significant myocardial ischemia as assessed by adenosine stress CMR (n = 35) and patients without myocardial ischemia (n = 74) there was no significant difference in the PCAT CT attenuation of RCA (-85.3 vs. -85.7 HU, p = 0.87), LAD (-84.8 vs. -85.7 HU, p = 0.66) and LCX (-82.8 vs. -83.2 HU, p = 0.79) as well as in the per patient PCAT CT attenuation (-84.2 vs. -84.9 HU, p = 0.76). Neither did patients with myocardial ischemia within the RCA territory show increased RCA PCAT CT attenuation (-87.7 vs. -85.3 HU, p = 0.40); nor was such a relationship found for the territory of the LAD (-80.6 vs. 85.8 HU, p = 0.11) or LCX (-83.1 vs. -83.0 HU, p = 0.99). The CT attenuation of EAT (-77.9 vs. -78.7 HU, p = 0.65) and PAT (-89.9 vs. -90.0 HU, p = 0.93) did not differ significantly between patients with myocardial ischemia compared to patients without myocardial ischemia. Between patients with myocardial ischemia and patients without myocardial ischemia there was no significant difference in the volumes of EAT (118.1 vs. 110.6 cm³, p = 0.55), PAT (279.5 vs. 240.9 cm³, p = 0.20) and the per patient PCAT volume (1021.9 vs. 1015.5 cm³, p = 0.90). In logistic regression analysis the volume and CT attenuation of the different intrathoracic fat compartments PCAT, EAT and PAT were not independently associated with the presence of myocardial ischemia (n.s.). Conclusions: In this single-centre study CTA-derived quantified CT attenuation and volume of PCAT, EAT and PAT were not associated with myocardial ischemia as assessed by adenosine stress CMR perfusion imaging.